1999
DOI: 10.1006/viro.1999.9675
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 E6 Oncoprotein Inhibits Apoptosis Induced during Serum–Calcium Differentiation of Foreskin Human Keratinocytes

Abstract: Transfection of human papillomavirus (HPV) 16 E6 oncogene into foreskin primary human keratinocytes (PHKs) causes the formation of colonies of viable cells resistant to serum-calcium differentiation. To define the stage of keratinocyte differentiation inhibited by E6, we examined the response of PHKs to serum and calcium with respect to parameters of both growth and differentiation. The effect of HPV16 E6 was evaluated by infection with recombinant retroviruses encoding the E6 protein. Results of these studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…TM -293 cells were infected with the recombinant retrovirus HPV16 E6, kindly provided by L. Sherman (46). The cells were grown to 75% confluence and infected at a multiplicity of infection of 2-5.…”
Section: Retroviral Infection Of T-rex Tm -293 Cells-for Constitutivementioning
confidence: 99%
“…TM -293 cells were infected with the recombinant retrovirus HPV16 E6, kindly provided by L. Sherman (46). The cells were grown to 75% confluence and infected at a multiplicity of infection of 2-5.…”
Section: Retroviral Infection Of T-rex Tm -293 Cells-for Constitutivementioning
confidence: 99%
“…The opposing effects of BPV-1 E6 and E7 may be implicated in the life cycle, replication, and maintenance of BPV-1. Recent studies have shown that the high-risk HPV-16 E6 and E7 oncogenes either increase or decrease apoptosis depending on the cell lines and apoptotic stimuli employed (Puthenveettil et al, 1996;Jones et al, 1997;Iglesias et al, 1998;Magal et al, 1998;Rapp and Chen, 1998;Stoppler et al, 1998;Alfandari et al, 1999;Liu et al, 2000b;Mannhardt et al, 2000;Finzer et al, 2002). Interestingly, while normal human diploid fibroblasts that express HPV-16 E7 are highly predisposed to undergo apoptosis in response to growth factor deprivation, they have decreased propensity to undergo apoptosis in response to TNF-and Fas treatment (Jones et al, 1997;Thompson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, keratinocyte differentiation has been successfully induced by several factors, such as osmotic stress, growth factors, high calcium concentrations, or serum supplementation [16,22,23,27,46]. To investigate whether the keratinocytes isolated from piglets retain the ability to differentiate in vitro after the isolation procedure, normal keratinocyte growth medium (EKGM) was replaced with a differentiation medium.…”
Section: Effect Of Calcium and Serum On Cell Differentiation Of Keratmentioning
confidence: 99%
“…By adjusting the plane of focus of the microscope, we were able to classify enlarged cells with a flattened morphology and a cornified envelope as differentiated cells. To induce differentiation, the medium was supplemented either with serum (SeDM) [23] or calcium (CaDM) [16]. Keratinocytes growing as a monolayer in low calcium (60 M) can be induced to terminally differentiate by adding calcium to the culture medium (> 1 mM).…”
Section: Porcine Keratinocytes Retain Their Ability To Differentiatementioning
confidence: 99%
See 1 more Smart Citation